Seroepidemiología de la diarrea viral bovina en los cantones Pangua, Pujilí, Saquisilí y Salcedo de la provincia de COTOPAXI. - Lagua Tubón, Edison Santiago (2023)
Bovine Viral Diarrhoea is an infectious disease that causes significant losses in cattle farming. The objective of this study was to evaluate the seroepidemiology of Bovine Viral Diarrhoea using the ELISA-i technique in backyard cattle in the cantons of Pangua, Pujilí, Saquisilí, and Salcedo in the province of Cotopaxi. A total of 238 backyard cattle of both sexes were sampled in the rural parishes of the cantons under study belonging to the province of Cotopaxi - Ecuador. The variables age and breed were incorporated as factors related to the prevalence of the disease. The samples were analyzed in the Faculty of Veterinary Medicine, Faculty of Agricultural Sciences and Natural Resources - Technical University of Cotopaxi laboratory using the ELISA-i technique. The data obtained were analyzed by the chi-square test using R software to determine the prevalence of BVD concerning risk factors. The study showed a prevalence of 39.91% in the four cantons, with a higher prevalence in Pujilí than in any other cantons evaluated. Only the race factor was statistically related to the disease. The epidemiological map allowed us to identify the geographical location of the positive animals.